Ser bacharel e professor: sentidos e relações entre o bacharelado e a docência universitária - Oliveira, Vivianne Souza de (2011)
The need to research about meanings and relationships between individuals with Bachelor s degrees and Teaching can be considered an exercise capable of aiding in the comprehension of the very performance of the Bachelor as teacher. The guiding question of this study asks: what relationships are established by Bachelors, who are teachers, between their professional education and their performance as a teacher? My objective is to understand the meanings attributed by the Bachelor teachers to teaching at the university level, seeking indicators about the relationships established by them, between their professional education and being a teacher. For this, the methodology used was the Comprehensive Interview, which permits, through the individual s oral discourse, the interpretation of meanings and values expressed by the teachers about their actions. The research is done through oral discourse collected in interviews and from these I analyze the elements that are revealed, and those which help me in the development of this object of study. I understand that the contribution about the possibilities of action and continued education for Bachelors who act as instructors in Higher Education is increasingly necessary, through research, because through continuing education teachers can revisit their actions and reformulate meanings they attribute to teaching as a profession. I consider the debate about meanings about teaching and the relationships with the initial education is not only necessary in the investigation of the Bachelors who act as professors, but also the credentialed teachers, because the teacher s sense of identity and their professional development is constructed through a historical process and in relation to the alternative positioning in the contexts of which they are a part